2000
DOI: 10.1038/78638
|View full text |Cite
|
Sign up to set email alerts
|

A controlled trial of intratumoral ONYX-015, a selectively-replicating adenovirus, in combination with cisplatin and 5-fluorouracil in patients with recurrent head and neck cancer

Abstract: ONYX-015 is an adenovirus with the E1B 55-kDa gene deleted, engineered to selectively replicate in and lyse p53-deficient cancer cells while sparing normal cells. Although ONYX-015 and chemotherapy have demonstrated anti-tumoral activity in patients with recurrent head and neck cancer, disease recurs rapidly with either therapy alone. We undertook a phase II trial of a combination of intratumoral ONYX-015 injection with cisplatin and 5-fluorouracil in patients with recurrent squamous cell cancer of the head an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
630
2
9

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 976 publications
(655 citation statements)
references
References 30 publications
14
630
2
9
Order By: Relevance
“…60 A controlled clinical trial in which recurrent head and neck cancer patients being treated with cisplatin and 5-FU were also treated with an oncolytic Ad demonstrated stasis in virally injected tumors, whereas all noninjected tumors treated with chemotherapy alone progressed. 11 In clinical trials, the response rate for tumors in patients treated with combinations improved compared to tumors in patients treated with chemotherapy alone. 13 There are several possible mechanisms underlying the synergy between virotherapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…60 A controlled clinical trial in which recurrent head and neck cancer patients being treated with cisplatin and 5-FU were also treated with an oncolytic Ad demonstrated stasis in virally injected tumors, whereas all noninjected tumors treated with chemotherapy alone progressed. 11 In clinical trials, the response rate for tumors in patients treated with combinations improved compared to tumors in patients treated with chemotherapy alone. 13 There are several possible mechanisms underlying the synergy between virotherapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…2,[6][7][8][9] Clinical trial data also suggest the utility of oncolytic Ads for the treatment of cancer. [10][11][12][13][14] Previously, we described the oncolytic Ad called Ar6pAE2fF, in which the E2F-1 promoter controls expression of E1A. 4 This oncolytic Ad was safe and efficacious when delivered intratumorally.…”
mentioning
confidence: 99%
“…One such vector is ONYX-015 that contains the E1a gene and uses viral genomic deletion for E1b 55k to interrupt the virus life cycle in the presence of cellular p53 (in normal cells) but not mutant p53 (found in many tumor cells). [7][8][9][10] Although ONYX-015 has shown potential in various laboratory and clinical studies, a lack of correlation between p53 status and viral replication has been reported. 15 Other vectors use tumor-specific promoters for E1 gene expression restricted to tumor cells to facilitate viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…Such vectors, that is, ONYX-015 (dl1520) with E1B55-deletion 7 and ONYX-411 containing E1 and E4 genes both under the control of human E2F promoter, 8 have achieved oncolytic effects in various tumors in clinical trials. [8][9][10] Despite this recent progress, adenovirus gene therapy for liver cancer continues to face challenges. Potential limitations include the lack of specific tumor surface markers necessary for viral targeting in liver tumors.…”
mentioning
confidence: 99%
“…Of note, ONYX-015 has shown activity against chemotherapy-resistant tumors in both preclinical and clinical studies. 16,22,24 Despite these findings, however, correlation of p53 function with efficacy has not been convincingly demonstrated in vivo to date. We therefore tested the sensitivity of tumor lines in vivo that were identical except for p53 status.…”
mentioning
confidence: 99%